2014
DOI: 10.1055/s-0033-1361186
|View full text |Cite
|
Sign up to set email alerts
|

Thermoregulation, Hydration and Performance over 6 Days of Trail Running in the Tropics

Abstract: International audienceThe purpose of this study was to investigate thermal response, hydration and performance over a 6-day, 142-km trail running race in tropical conditions. 9 participants competed in the 2011 Gwadarun (30 °C ± 2.4 °C and 82 ± 4 % RH). Data were collected on days 1, 4 and 6. Gastrointestinal temperature (T gi ) and heart rate (HR) were measured using portable telemetry units, whereas blood samples were collected for hematocrit, osmolarity, plasma concentrations, alkaline reserves and creatine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(22 citation statements)
references
References 38 publications
(24 reference statements)
1
19
0
2
Order By: Relevance
“…It thus seems clear that these subjects, despite great TBWL (0.5-2.7 L) associated with a mean 0-1.5 L of WI inducing a 0.3-1.3 kg loss (mean 0.4-1.8% of body mass loss), did not present severe dehydration or heat illness while drinking ad libitum as described in the literature in high-level marathoners [10], standard runners [17], and recently in IRP [9]. Taken together, these findings reinforce the view that ad libitum hydration is enough for endurance exercise in a hot environment [17, 21, 22, 23]. These results could be surprising if we consider that average-range athletes normally drink at a higher rate than high-level or more trained ones [24, 25].…”
Section: Discussionsupporting
confidence: 78%
“…It thus seems clear that these subjects, despite great TBWL (0.5-2.7 L) associated with a mean 0-1.5 L of WI inducing a 0.3-1.3 kg loss (mean 0.4-1.8% of body mass loss), did not present severe dehydration or heat illness while drinking ad libitum as described in the literature in high-level marathoners [10], standard runners [17], and recently in IRP [9]. Taken together, these findings reinforce the view that ad libitum hydration is enough for endurance exercise in a hot environment [17, 21, 22, 23]. These results could be surprising if we consider that average-range athletes normally drink at a higher rate than high-level or more trained ones [24, 25].…”
Section: Discussionsupporting
confidence: 78%
“…However, the main factor for heat production is exercise intensity (Racinais et al, 2019) and longer events may be less prone to hyperthermia in a given environment, as they are performed at a lower intensity. For example, a study on 31 heat-acclimated male soldiers participating in a half marathon in tropical environment revealed that 68% of the finishers completed the race with a gastrointestinal temperature > 40 • C (Lee et al, 2010), while in a 142 km trail run performed over 6 days in tropical environment, the maximal gastrointestinal temperature was only 38.3-38.7 • C (Hue et al, 2014). These findings warrant specific field research during ultra-endurance events in hot and humid ambient conditions to characterize the thermal responses to various race situations.…”
Section: Metabolic Heat Production and Core Temperaturementioning
confidence: 99%
“…Průměrný pozorovaný příjem sledovaných sportovců 0,55 ± 0,34 l/h sice koresponduje s doporučeními ACSM z r. 2007 (0,4-0,8 l/h), ovšem odhadované ztráty tělesné hmotnosti (dehydratace) v rozsahu 6,6-11,7 % 1 v relativně příznivých klimatických podmínkách ~15 °C je zcela mimo "tolerovaný limit 2 %". Nepřímá závislost mezi mírou poklesu hmotnosti a výsledným časem je doložena také u rekreačních maratonských běžců (Zouhal et al, 2010), 6denního horského běžeckého závodu v tropických podmínkách (Hue, Henri, Baillot, Sinnapah, & Uzel, 2014), ale i u kratších běžeckých distancí (11,3 km) (Adams et al, 2016). Uvedené příklady jsou reálným důkazem rozporu mezi teorií a praxí zejména ve vrcholovém sportu.…”
Section: Existuje Hranice Dehydratace Limitující Výkon?unclassified
“…dálkové plavání). Autoři dále konstatují, že dehydratace se pouze minimálně podílí na vzestupu tělesné teploty v průběhu zatížení, s výjimkou vzestupu intragastrické teploty, která sice vzrůstá lineárně s poklesem tělesné hmotnosti, ovšem její potenciální dopady na sportovní výkon nejsou blíže popsány (Hue et al, 2014).…”
Section: Autonomní Příjem Tekutin a Vytrvalostní Výkonunclassified